Fabrication and Characterization of Collagen-Immobilized Porous PHBV/HA Nanocomposite Scaffolds for Bone Tissue Engineering. (9th April 2012) - Baek, Jin-Young; Xing, Zhi-Cai; Kwak, Giseop; Yoon, Keun-Byoung; Park, Soo-Young; Park, Lee Soon; Kang, Inn-Kyu
Abstract : The porous composite scaffolds (PHBV/HA) consisting of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and hydroxyapatite (HA) were fabricated using a hot-press machine and salt-leaching. Collagen (type I) was then immobilized on the surface of the porous PHBV/HA composite scaffolds to improve tissue compatibility. The structure and morphology of the collagen-immobilized composite scaffolds (PHBV/HA/Col) were investigated using a scanning electron microscope (SEM), Fourier transform infrared (FTIR), and electron spectroscopy for chemical analysis (ESCA). The potential of the porous PHBV/HA/Col composite scaffolds for use as a bone scaffold was assessed by an experiment with osteoblast cells (MC3T3-E1) in terms of cell adhesion, proliferation, and differentiation. The results showed that the PHBV/HA/Col composite scaffolds possess better cell adhesion and significantly higher proliferation and differentiation than the PHBV/HA composite scaffolds and the PHBV scaffolds. These results suggest that the PHBV/HA/Col composite scaffolds have a high potential for use in the field of bone regeneration and tissue engineering.